UJI EFEKTIVITAS ANTIBAKTERI NANO GEL BAHAN AKTIF EKSTRAK KAYU MANIS (Cinnamomum burmannii) TERHADAP Staphylococcus aureus - Purwandari, Vivi; Sianipar, Artha Yuliana; Silalahi, Yosy Cinthya Eriwaty; Nasution, Dinda Juita (Jurnal Farmanesia, 2020)
Nanogel preparations consist of nanoemulsions and gels, where nanoemulsion is one type of preparation that can increase drug permeability on the membrane surface. The use of cinnamon extract as an antibacterial active substance is because cinnamon (Cinnamomum burmannii) contains saponins, tannins, and flavonoids. This study aims to make nanogel preparations with the active ingredient of cinnamon extract and to determine the antibacterial effectiveness of the nanogel as the active ingredient of the cinnamon extract against Staphylococcus aureus. The manufacture of 2% cinnamon extract nanoemulsion aims to make nanoparticle-sized nanogel preparations and as an antibacterial active substance in nanogel preparations against Staphylococcus aureus bacteria. Nanogel preparations were made by adding cinnamon extract nanoemulsion with varying concentrations of F1(2%), F2(4%), F3(6%), and blank formula (F0) as the basis for nanogels without cinnamon extract nanoemulsion. The results showed that the cinnamon extract nanoemulsion could be made into nanogels to produce a thick, brown-colored gel with a characteristic cinnamon smell. The result of the pH of the preparation is 6 according to the pH of the skin, has good homogeneity, and is not irritating to the skin. The PSA test produces a nanoparticle size of 24.2 nm, and the antibacterial effectiveness test of the nanogel preparation can inhibit Staphylococcus aureus bacteria. Produced a moderate inhibition zone category (6.7-7.1 mm) and the F3 formulation (6%) was the best formulation.